PENGEMBANGAN MODEL PEMBELAJARAN LARI FORMULA DENGAN PENDEKATAN PERMAINAN BENTENG PORTUGIS PADA SISWA KELAS V SD N 3 BANYUMANIS KECAMATAN DONOROJO KABUPATEN JEPARA TAHUN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
Learning facilities and infrastructure in Penjasorkes very limited, and many of the studentsdo not like learning Penjasorkes. To overcome these problems, the need for developing alternativelearning approaches run game formula with the Portuguese fort. This study is a researchmethod development. The analysis procedure includes product development product that willbe developed, developing initial products, expert validation and revision, testing and revisionsmall group, large group and test the final product. The data was collected using field observationsand questionnaires were obtained from expert evaluation and the results of the questionnairesby students. The data analysis technique used is descriptive percentages. From thetest results obtained by the expert evaluation data, expert penjas with percentages of 85.3%, apercentage of the learning I with 82.6%, a percentage of the learning II with 84.66%, smallgroup testing 83.78%, and the test 91.67% of the group try to criteria (excellent).Based on the research data, it was concluded that the Portuguese fortress game effectively andin accordance with the characteristics of the students so that they can be applied as a modelof learning in the learning Penjasorkes. Expected for primary school teachers Penjasorkes 03Banyumanis can use the product model of the Portuguese fort games in the learning process.